Dlouhodobé výsledky operace dle Ludloffa ve vztahu k operačnímu nálezu na labrum acetabulare - Popelka, Stanislav; Popelka, Stanislav; Barták, Vladislav; Fulín, Petr; Pokorný, David; Sosna, Antonín (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2018)
PURPOSE OF THE STUDY Developmental dysplasia of the hip still remains one of the most discussed topics in paediatric orthopaedics. The comprehensive care of paediatric patients with congenital developmental dysplasia of the hip at our department in the period from 1970 to 1985 included, among other things, the open reduction using Ludloff s approach in hip joints where closed reduction was not possible. This technique was supported by some of our own previous observations, such as the original classification of intraoperative findings on acetabular labrum (limbus). This study aims to evaluate the long-term results of treatment of our patients where Ludloff s open reduction was used and seeks to establish a conclusive correlation between the final result and the method of treatment of individual types of limbus, possibly confirming or ruling out that the dependence of later development of the acetabulum is dependent on correct and sparing treatment of this barrier to reduction. MATERIAL AND METHODS In the period from 1970 to 1985, the Ludloff s open reduction was performed in 70 patients. In 8 cases bilateral surgery was carried out. A total of 78 hip joints were operated on. The patients underwent the surgery at the age of 5-23 months. Postoperatively, the Hanausek biomechanical apparatus was applied to complete the treatment. In total, documentation of 21 surgeries performed in 20 patients was successfully tracked down. Two patients were removed from the group for incomplete documentation. The final group of patients included a total of 18 patients, of whom there were 13 women and 5 men. In one female patient the surgery was performed bilaterally. The shape of the femoral head, the center-edge (CE) angle and the degree of osteoarthritic changes were assessed on the pelvic radiograph of each patient. The functional result was evaluated using the Harris Hip Score (HHS). RESULTS For the purpose of assessment, the patients were divided into sub-groups based on the intraoperative finding on acetabular labrum. Type I limbus was found in a total of 5 cases. The mean HHS was 93, the mean CE angle was 22.5°. Aseptic necrosis occurred in one patient. Type II limbus was found in a total of 3 patients. The mean HHS was 84, the mean CE angle was 22°. Aseptic necrosis was observed in one patient. Type III limbus was found in 8 patients. The mean HHS was 79, the mean CE angle was 19.4°. Osteoarthritic changes of degree II-III were identified. Necrosis of the femoral head was recorded in 2 patients. Type IV limbus was found three times. The mean HHS was 73, the mean CE angle was 13.3°. Osteoarthritic changes of type III were present. Necrosis of the femoral head was recorded altogether in 2 patients. DISCUSSION The results of the Ludloff procedure reported in the available literature differ markedly as to the resulting function of the hip joint and the incidence of avascular necrosis. No author gave a description of the actual acetabular labrum deformity or showed a detailed description of individual vessel ligations. The advantage of this method is beyond any doubt its low invasiveness and when correctly performed also the minimal burden to the child. Its disadvantage is a certain degree of difficulty in performing this surgery, a worse visualisation of all barriers to reduction and a more challenging treatment of the posterior portion of the hip joint compared to techniques using the anterior approach. CONCLUSIONS Our outcomes indicate that the resulting Harris Hip Score was best in patients with the intraoperative finding of type I limbus. All the other types (ll-IV) showed worse HHS results. From the current perspective, it is in all likelihood more advantageous to use surgical approaches that enable better visualisation of the anatomical deformities and allow for better options for their treatment.
Keywords: Acetabulum; acetabulum; vývojová kyčelní dysplazie; lidé; Female; mužské pohlaví; Infant; Male; kojenec; Hip Dislocation, Congenital; ženské pohlaví; otevřená repozice dle Ludloffa; Humans